Surface and subsurface reworking by storms on a Cambrian carbonate platform: evidence from limestone breccias and conglomerates - Chen, Jitao (Geologos, 2014)
Some limestone breccias and conglomerates from the Furongian (Late Cambrian) Chaomidian Formation (Shandong Province, China) were investigated in order to understand the depositional and deformational processes induced by storms. The sediments under study occur in a hummocky cross-stratified peloidal grainstone layer. The limestone conglomerates consist of well-rounded clasts that are mostly flat-lying or imbricated, and have erosional bases. They formed by surface reworking (erosion and rip-up) of thin-bedded grainstones by storm waves and currents. The limestone breccias consist of subangular to subrounded clasts of grainstone, which are often associated with small-scale grainstone clastic dykes. The breccias and dykes resulted from subsurface soft-sediment deformation (i.e., differential liquefaction and fluidization of heterogeneously cemented carbonate grains), most likely triggered by storm-wave loading. The limestone breccias and conglomerates bear important implications for understanding the reworking mechanisms of storms on ancient carbonate platforms.